2015
DOI: 10.1039/c4ra17140c
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation and thermal gelation of N-isopropylacrylamide based cucurbit[7]uril side-chain polypseudorotaxanes with low pseudorotaxane content

Abstract: Low pseudorotaxane content (≤3 mol%) endows N-isopropylacrylamide based cucurbit[7]uril polypseudorotaxanes unique aggregation and thermal gelation properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…In an interesting example of three-dimensional structure, aggregation of N -isopropylacrylamide (NIPAAM) thermogels has been controlled by introducing CB[7] as polypseudorotaxane side chains. Such inclusion results in semirigid polymer segments that induce transition from a globular to porous morphology that could be observed by optical microscopy in a hydrated state . Control of physical structure on these length scales holds great promise for the cell biology and biomaterials fields, as dynamic self-assembly of these structures may best recapitulate the natural processes that drive cell behavior.…”
Section: Structure Of Self-assemblymentioning
confidence: 99%
“…In an interesting example of three-dimensional structure, aggregation of N -isopropylacrylamide (NIPAAM) thermogels has been controlled by introducing CB[7] as polypseudorotaxane side chains. Such inclusion results in semirigid polymer segments that induce transition from a globular to porous morphology that could be observed by optical microscopy in a hydrated state . Control of physical structure on these length scales holds great promise for the cell biology and biomaterials fields, as dynamic self-assembly of these structures may best recapitulate the natural processes that drive cell behavior.…”
Section: Structure Of Self-assemblymentioning
confidence: 99%
“…21 Experimentally, recent reports have indicated that bulk physical hydrogels can form heterogeneous structures, including those formed through macrocyclic assembly. 22-26 Despite this work, there remains a lack of experimental investigation to bridge the gap between directed polymeric self-assembly and supramolecular microstructures.…”
Section: Introductionmentioning
confidence: 99%
“…Many applications such as the development of injectable and printable hydrogels are closely linked to this characteristic 1 2 3 . In order to meet this goal, gelation mechanisms that are based on physical changes including temperature 4 5 , ionic strength 6 7 , pH value 8 , shear force 9 , and chemical reactions such as the Schiff base formation 10 11 , disulfide bond formation 12 , Michael addition 13 and photopolymerization 14 15 16 have been explored 17 . However, it remains a challenge to have effective control over gelation kinetics without compromising the structure and other properties of hydrogels.…”
mentioning
confidence: 99%
“…However, it remains a challenge to have effective control over gelation kinetics without compromising the structure and other properties of hydrogels. Although the gelation of hydrogels based on physical changes is triggered by external stimuli, their gelation usually proceeds through a sharp transition when the corresponding external stimuli are applied 4 5 6 7 8 . Control over the gelation kinetics of hydrogels based on chemical reactions is plausible.…”
mentioning
confidence: 99%